Типи народних сорочок Гетьманських земель Лівобережжя (із фондової збірки Музею народної архітектури та побуту НАН України) - Шафранська, Г. (Народна творчість та етнографія, 2006)
Ukraine is well-known in Europe by its art of song, dance and folk crafts. But Ukrainian traditional embroidered shirt is considered to be the most typical national symbol. The goal of professionals engaged in the fields of culture, education and science is to preserve, study and develop the original art of embroidery. In this paper the author gives a brief review of the main types of embroidered shirts and ways of decoration used during last two centuries on the territories of Hetmanate - historical area in the left-bank Ukraine.